Structural, magnetic and photoluminescence properties of new hybrid hypophosphites: discovery of the first noncentrosymmetric and two cobalt-based members. Issue 23 (6th June 2022) - Mączka, Mirosław; Gągor, Anna; Stefańska, Dagmara; Zaręba, Jan K.; Pikul, Adam
Abstract : Hybrid hypophosphite perovskites exhibiting ferromagnetism, polar order and photoluminescence. Abstract : Hybrid organic–inorganic perovskites comprising hypophosphite ligands are emerging functional materials exhibiting magnetic, photoluminescence, negative thermal expansion and negative linear compressibility behaviours. This work reports five novel hypophosphite perovskites, [A]M(H2 POO)3 (A = pyrrolidinium (PYR + ), guanidinium (GUA + ) and imidazolium (IM + ); M = Cd 2+ and Co 2+ ). [GUA]Cd(H2 POO)3, [IM]Cd(H2 POO)3, [GUA]Co(H2 POO)3 and [IM]Co(H2 POO)3 belong to the centrosymmetric trigonal R 3̄ c, monoclinic P 21 / c, monoclinic I 2/ m, and orthorhombic Pbca space groups, respectively, while [PYR]Cd(H2 POO)3 crystallizes in the noncentrosymmetric orthorhombic space group Aea 2. The polar order of PYR + cations was confirmed by observation of moderate second harmonic generation (SHG) activity. Magnetic studies reveal that [GUA]Co(H2 POO)3 and [IM]Co(H2 POO)3 are weak ferromagnets with the ordering temperatures higher compared to their manganese analogues. Upon ultraviolet excitation, the cadmium counterparts exhibit purplish-blue emissions at low temperatures, which decrease on heating. Analysis of the photoluminescence data reveals that the emission quenching decreases with decreasing distortion of the cadmium–hypophosphite framework. Discovery of the new hypophosphites exhibiting magnetic or polar order and photoluminescence properties shows that hypophosphite perovskites offer a promising platform for generating new functional materials, including those that are light emitting, ferroelectric and multiferroic.